2020
DOI: 10.3390/toxics8020038
|View full text |Cite
|
Sign up to set email alerts
|

E-Cigarette Liquid Provokes Significant Embryotoxicity and Inhibits Angiogenesis

Abstract: E-cigarette smoking (ECS) is a new method of tobacco smoking that is gaining popularity as it is thought to be a “healthy method” of tobacco consumption. The adverse outcomes of ECS on the respiratory and cardiovascular systems in humans have been recently demonstrated. Nevertheless, the effect of e-cigarette liquid (ECL) on the early stage of embryogenesis and angiogenesis has not been explored yet. Chicken embryo at 3 days of incubation and its chorioallantoic membrane (CAM) of 5 days were used to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Alternatively, extracts from electronic cigarettes have been tested for their effect on angiogenesis and embryo development in the chorioallantoic membrane. Research has established that the extracts killed 70% of the embryos after a 5 day exposure period and, in addition, inhibited angiogenesis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, extracts from electronic cigarettes have been tested for their effect on angiogenesis and embryo development in the chorioallantoic membrane. Research has established that the extracts killed 70% of the embryos after a 5 day exposure period and, in addition, inhibited angiogenesis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with HPV-negative OPSCC are known for high nicotine consumption throughout their lifetime. Ashour and colleagues showed that nicotine upregulates INHBA in chicken embryos ( 27 ). Hence, INHBA overexpression could be attributed to nicotine consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of nicotine are dose-dependent, and it was found that while high doses inhibit cell division, low doses could stimulate angiogenesis therefore other dominant chemicals present in cigarette smoke could be responsible for decreased cell division and vessel growth [32]. A recent study has observed that E-cigarette liquid inhibits angiogenesis of the CAM for 5 days due to the upregulation of ATF-3, FOXA2, INHBA, MAPRE-2, and RIPK-1 and downregulation of SERPINA-4 AND VEGF-C genes necessary for embryogenesis as well as angiogenesis [35]. Investigation of pulmonary arteries during chick embryo development in the presence of cigarette smoke extract impaired endothelium-dependent vasodilation proving the effect of cigarette smoke on fetal vascular endothelial vasorelaxant pathways causing the development of pulmonary hypertension in the newborn [36].…”
Section: Abnormal Angiogenesismentioning
confidence: 99%